Governo Eletrônico: Uma proposta para avaliação dos serviços governamentais eletrônicos sob o prisma da usabilidade - Melo, Luciana Alves de (2018)
This paper approaches the development of a checklist designed to evaluate Brazilian e-government portals according to a specific dimension defined as usability. The research is jus-tified precisely due to the e-Government program (e-Gov) of the Federal Government has im-plemented strategies with recommendations of good practices in the digital area, from which it is possible to identify the errors and difficulties encountered by the users to correct and thus, making e-Govs easier to use. The elaboration of the checklist, as a result of this study, initially comprised a structured documental research, with the purpose of identifying the pecu-liarities of these conventions created to guide the developers of web interfaces within the scope of Public Administration. Therefore, the objective of this research corroborated the con-struction of this updated checklist, merging other evaluation models of electronic government services found in the literature related to the usability dimension and applicable to the devel-opment of websites or portals; Due to the nature of the research objectives, a qualitative and exploratory research was carried out, adopting the approach of multi-domain studies (YIN, 2001) in three e-government portals at the federal level to apply the developed checklist. The choice of the portal of the Federal University of Uberlândia was then selected for pilot test-ing, because the researcher decided to fit within the purpose of the Professional Master's Pro-gram, to which it is linked, which concerns the generation of products with a more practical application within the work environment itself. In addition to this portal, by similarity of tar-get audience, two other portals were chosen with the intention of making a brief and succinct comparison. The results pointed out the strengths and weaknesses of the portals and rein-forced the importance of usability principles in the projects as a factor of great relevance in the satisfaction of the users. Finally, the study allowed the recognition of factors associated with usability that help improve the quality of government electronic services and therefore should be incorporated into e-Govs of all public spheres. From this paper, a checklist was created as a technological product that aims to improve the delivery of government electronic services.